Social Well-Being of Higher School Teachers: Social Context and Measurement Criteria - L. A. Osmuk; V. A. Yablonskaya (Высшее образование в России)
The article is considered the problem of the university teachers’ social well-being, that is connected with significant and continuous changes in the social context of the development of the high education institution. Two issues are raised: about the complicated situation (context) and negative determinants impact on the teachers social well-being, and, accordingly, about the relevant criteria for measuring the social well-being in the studied professional group under the current conditions. It is explained that the complex social context and the observed changes in the teachers social well-being are determined by the ratio of objective and subjective factors: the increase in the number of risks and the rapid development of society affect not only the teachers’ status, but also how they aware themselves in these conditions. To confirm the thesis about a possible decrease in social well-being against the background of everincreasing social threats, the results of a sociological survey conducted at the Novosibirsk State Technical University using the questionnaire method (n = 327) are presented. According to these results, most teachers get satisfaction from their work and, above all, work with students, but the frequent changes in the concepts of higher education and emergence of external threats negatively affect the state of social well-being. Although slightly more than half “probably wouldn’t change” their profession for any other, not everyone can fully adapt to the new and constantly changing higher education system requirements. The positive socio-psychological climate in the subdivisions acts as a protective barrier against external threats. In general, the results obtained give reason to think about the need to monitor the state of social well-being of teachers in the process of modernizing the higher education system and create appropriate conditions for successful scientific and educational activities.